Badminton Athlete in Marketing Communication Strategy: Study of Bank Mandiri Ads on Youtube - Ainani, Muhammad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This paper seeks to analyze and study further about how the marketing strategy is carried out by utilizing badminton athletes in advertisements carried out by Bank Mandiri. This is important to do as an evaluation material for marketing communication strategies carried out in the new media era, because the object of research is taken from videos on the Yotube platform. The focus of the research will be on three advertising videos on Bank Mandiri's Youtube channel which were uploaded on November 5, 2018 – February 10, 2019. The results show that the use of badminton athletes as commercial star for Bank Mandiri is a marketing communication strategy that has been carefully calculated. If referring to the concept of marketing communication strategy, namely segmentation, targeting, and positioning. It can be seen that Bank Mandiri has implemented its marketing communication strategy well and effectively. The strong position of the three athletes in forming a brand image is the reason for Bank Mandiri to use the three as commercial star. It is hoped that the strong brand image of the three athletes can influence the corporate image of Bank Mandiri so that it can imitate the image of the three who are already strong, namely young, millennial, and high achievers.